Gut Metagenome as a Potential Diagnostic and Predictive Biomarker in Slow Transit Constipation - Tian, Hongliang; Ye, Chen; Yang, Bo; Cui, Jiaqu; Zheng, Zhijun; Wu, Chunyan; Zhou, Shailan; Lv, Xiaoqiong; Qin, Nan; Qin, Huanlong; Li, Ning; Chen, Qiyi (Frontiers in Medicine, 2022)
Slow transit constipation (STC) is a common functional disorder and it represents a huge health care burden because of the high prevalence and long-term duration.In this study, we performed metagenome sequencing analysis of 118 stool samples from 66 STC individuals and compared their microbial profiles with those of 52 healthy subjects. We found that the intestinal microbiome of STC patients was significantly different from that of healthy individuals at the phylum, genus, and species level. STC patients had markedly higher levels of Alistipes and Eubacterium, and lower abundance of multiple species belonging to the Roseburia genus. STC patients’ gene expression levels and KEGG orthology pathway enrichment were also substantially different from those of healthy controls. The most abundant KEGG orthologs in both groups were those associated with the fatty acid biosynthesis, butanoate metabolism, and methane metabolism pathways. These microbiome and metabolite differences may be valuable biomarkers for STC. Our results provide new avenues for the development of novel diagnostic tools and potential treatments. Furthermore, our findings suggest that alteration of the microbiome may lead to constipation by changing the levels of microbial-derived metabolites in the gut.